The Prevalence of Clubfoot in the Neonates who were Referred to the Emergency Department of Mofid Children Hospital - SEYYED HOSSEIN ZADEH ARDEBILI, Hamid Reza; HASSASS YEGANEH, Mehrnoush; IMAN ZADEH, Farid; BIGDELI, Mohammad Reza; OKHOVVATPOUR, Mohammad Ali (Iranian Journal of Child Neurology, 2011)
Objective Club-foot is one of the most prevalent congenital anomalies of the lowerextremities. Since there is no epidemiologic study on the prevalence of thisdisease in Iran, we decided to assess it in a sample population in Tehran. Materials and Methods We assessed all neonates who were referred to the emergency department ofmofid children hospital between October 2007 and November 2008, due to apaediatric emergency problem. None of the patients had chief complaints oflower extremity deformity. Results During this time period (13 months), we could examine 682 neonates. Noneof the parents of these neonates had complaints regarding anomaly of lowerextremities of their neonates at the time of the emergency referral. Of them, 371(54%) were female and 311 (46%) were male. The age of the mother at the timeof pregnancy was < 20 yr in 124 (18%) neonates, between 20 and 35 yr in 472(69%) neonates and > 35 yr in 86 (13%) neonates. There was a previous historyof clubfoot in the siblings of one of the neonates who was under orthopaedictreatment.Among all these neonates, we found two cases of clubfoot (0.3%), with bilateralinvolvement. In one of these cases, the older sibling also had clubfoot. Conclusion The incidence of clubfoot has been reported between 0.39 and 6 cases in 1000live birth in the literature. In the present study, we found a prevalence of 0.3 forclubfoot in every 1000 neonates. Keywords: Clubfoot; prevalence; congenital; talipesequinovarus.